Quantitative trait locus mapping of human blood pressure to a genetic region at or near the lipoprotein lipase gene locus on chromosome 8p22. - Wu, D A (1996)
Resistance to insulin-mediated glucose disposal is a common finding in patients with non-insulin-dependent diabetes mellitus (NIDDM), as well as in nondiabetic individuals with hypertension. In an effort to identify the generic loci responsible for variations in blood pressure in individuals at increased risk of insulin resistance, we studied the distribution of blood pressure in 48 Taiwanese families with NIDDM and conducted quantitative sib-pair linkage analysis with candidate loci for insulin resistance, lipid metabolism, and blood pressure control. We found no evidence for linkage of the angiotensin converting enzyme locus on chromosome 17, nor the angiotensinogen and renin loci on chromosome 1, with either systolic or diastolic blood pressures. In contrast, we obtained significant evidence for linkage or systolic blood pressure, but not diastolic blood pressure, to a genetic region at or near the lipoprotein lipase (LPL) locus on the short arm of chromosome 8 (P = 0.002, n = 125 sib-pairs, for the haplotype generated from two simple sequence repeat markers within the LPL gene). Further strengthening this linkage observation, two flanking marker loci for LPL locus, D8S261 (9 cM telomeric to LPL locus) and D8S282 (3 cM centromeric to LPL locus), also showed evidence for linkage with systolic blood pressure (P = 0.02 and 0.0002 for D8S261 and D8S282, respectively). Two additional centromeric markers (D8S133, 5 cM from LPL locus, and NEFL, 11 cM from LPL locus) yielded significant P values of 0.01 and 0.001, respectively. Allelic variation around the LPL gene locus accounted for as much as 52-73% of the total interindividual variation in systolic blood pressure levels in this data set. Thus, we have identified a genetic locus at or near the LPL gene locus which contributes to the variation of systolic blood pressure levels in nondiabetic family members at high risk for insulin resistance and NIDDM.